PENGUATAN PENDIDIKAN KARAKTER BERBASIS BUDAYA SEKOLAH GUNA MENINGKATKAN DAYA SAING PESERTA DIDIK (STUDI KOMPARASI SDN 037 TARAKAN INDONESIA DAN CHIANG RAI MUNICIPALITY SCHOOL 2 THAILAND) - Rizna Rizna; Muhammad Yunus; Agustinus Toding Bua (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2019)
Abstract: This research type is about descriptive qualitative research was conducted at SDN 037 Tarakan Indonesia and Chiang RaiMunicipality School 2 Thailand in the 2018/2019 school year. The focusof this study is the implementation of Character EducationStrengthening based on school culture in order to improve thecompetitiveness of students. The second research focus is thedevelopment of character values in order to improve the competitivenessof students at SDN 037 Tarakan Indonesia and Chiang Rai MunicipalitySchool 2 Thailand. The results of this research are the implementationof Strengthening Character Education to Increase Competitiveness ofStudents at SDN 037 Tarakan Indonesia and Chiang Rai MunicipalitySchool 2 Thailand. The second result is the development of charactervalues based on the five main values of Strengthening CharacterEducation, namely religious, nationalist, independent, mutualcooperation and integrity which in its development there are similaritiesand differences in the forms of development that are influenced byschool culture and trust in each country.Keywords: Strengthening Character Education, School Culture,Competitiveness, Comparative Studies.